2020
DOI: 10.7554/elife.54455
|View full text |Cite
|
Sign up to set email alerts
|

Pull-push neuromodulation of cortical plasticity enables rapid bi-directional shifts in ocular dominance

Abstract: Neuromodulatory systems are essential for remodeling glutamatergic connectivity during experience-dependent cortical plasticity. This permissive/enabling function of neuromodulators has been associated with their capacity to facilitate the induction of Hebbian forms of long-term potentiation (LTP) and depression (LTD) by affecting cellular and network excitability. In vitro studies indicate that neuromodulators also affect the expression of Hebbian plasticity in a pull-push manner: receptors coupled to the G-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In these studies, an elaborated set of possible mechanisms including LTP and LTD (Cooke & Bear, 2014) are invoked to explain the unexpected. A most recent study in mice (Hong, Huang, Severin, & Kirkwood, 2020) suggests that rapid bidirectional changes in OD with monocular stimulation are explained by the differential action of two types of designer receptors exclusively activated by designer drugs (DREADDs): activation of G q ‐DREADDs strongly suppresses the stimulated‐eye responses, resulting in a large decrease in imaging‐based ODI (ocular dominance index),[(Contralateral‐eye response, C − ipsilateral‐eye response, I)/(C + I)], while G s DREADDs enhances the stimulated‐eye responses, leading to a large increase in ODI. They suggest that the push‐pull action of two types of G protein‐coupled receptors, G q which coupled to α1‐adrenorecotors and G s to ß‐adrenoreceptors, underlies the observed changes in ODI.…”
Section: A Conceptual Issue: Tests Of Odp Per Sementioning
confidence: 99%
“…In these studies, an elaborated set of possible mechanisms including LTP and LTD (Cooke & Bear, 2014) are invoked to explain the unexpected. A most recent study in mice (Hong, Huang, Severin, & Kirkwood, 2020) suggests that rapid bidirectional changes in OD with monocular stimulation are explained by the differential action of two types of designer receptors exclusively activated by designer drugs (DREADDs): activation of G q ‐DREADDs strongly suppresses the stimulated‐eye responses, resulting in a large decrease in imaging‐based ODI (ocular dominance index),[(Contralateral‐eye response, C − ipsilateral‐eye response, I)/(C + I)], while G s DREADDs enhances the stimulated‐eye responses, leading to a large increase in ODI. They suggest that the push‐pull action of two types of G protein‐coupled receptors, G q which coupled to α1‐adrenorecotors and G s to ß‐adrenoreceptors, underlies the observed changes in ODI.…”
Section: A Conceptual Issue: Tests Of Odp Per Sementioning
confidence: 99%
“…7a). We used intrinsic signal imaging to evaluate cortical responses in the binocular zone of V1 as described 24, 25 . Cortical responses in mice are normally biased toward the contralateral eye and this bias is reduced by MD, reflected as a shift of the ocular dominance index (ODI, see methods).…”
Section: Resultsmentioning
confidence: 99%
“…Initially neuromodulators were thought as permissive/enabling factors that promote the induction Hebbian synaptic plasticity via the enhanced cellular and network excitability associated with arousal and the awake state. It was later found that besides facilitating it, specific neuromodulators can also act directly at the level of the expression of plasticity to control its magnitude and polarity 45,46 . Aligned with this latter idea, disruptions of the serotonergic system or the noradrenergic system during ODP respectively prevent the closed-eye depression of the non-deprived eye response potentiation 47 .…”
Section: Discussionmentioning
confidence: 99%